Factors associated with prolonged time to treatment failure with fulvestrant 500 mg in patients with post-menopausal estrogen receptor-positive advanced breast cancer: a sub-group analysis of the JBCRG-C06 Safari study. (2nd January 2018) - Kawaguchi, Hidetoshi; Masuda, Norikazu; Nakayama, Takahiro; Aogi, Kenjiro; Anan, Keisei; Ito, Yoshinori; Ohtani, Shoichiro; Sato, Nobuaki; Saji, Shigehira; Takano, Toshimi; Tokunaga, Eriko; Nakamura, Seigo; et al.
Abstract: Objective: The JBCRG-C06 Safari study showed that earlier fulvestrant 500 mg (F500) use, a longer time from diagnosis to F500 use, and no prior palliative chemotherapy were associated with significantly longer time to treatment failure (TTF) among Japanese patients with estrogen receptor-positive (ER+) advanced breast cancer (ABC). The objective of this sub-group analysis was to further examine data from the Safari study, focusing on ER + and human epidermal growth factor receptor-negative (HER2−) cases. Methods: The Safari study (UMIN000015168) was a retrospective, multi-center cohort study, conducted in 1, 072 patients in Japan taking F500 for ER + ABC. The sub-analysis included only patients administered F500 as second-line or later therapy ( n  = 960). Of these, 828 patients were HER2−. Results Multivariate analysis showed that advanced age (≥65 years; p  = .035), longer time (≥3 years) from ABC diagnosis to F500 use ( p  < .001), no prior chemotherapy ( p  < .001), and F500 treatment line ( p  < .001) were correlated with prolonged TTF (median = 5.39 months). Conclusions: In ER+/HER2− patients receiving F500 as a second-line or later therapy, treatment line, advanced age, no prior palliative chemotherapy use, and a longer period from ABC diagnosis to F500 use were associated with longer TTF.